Prophylactic Effect of Rebamipide on Aspirin-Induced Gastric Lesions and Disruption of Tight Junctional Protein Zonula Occludens-1 Distribution - Takahiro Suzuki; Norimasa Yoshida; Nami Nakabe; Yutaka Isozaki; Hirokazu Kajikawa; Tomohisa Takagi; Osamu Handa; Satoshi Kokura; Hiroshi Ichikawa; Yuji Naito; Hirofumi Matsui; Toshikazu Yoshikawa (Elsevier, 2008)
Aspirin and nonsteroidal anti-inflammatory agents are known to induce gastroduodenal complications such as ulcer, bleeding, and dyspepsia. In this study, we examined the prophylactic effect of rebamipide, an anti-ulcer agent with free-radical scavenging and antiinflammatory effect, on acidified aspirin-induced gastric mucosal injury in rats. In addition, we investigated the mucosal barrier functions disrupted by aspirin. Oral administration of acidified aspirin resulted in linear hemorrhagic erosions with increasing myeloperoxidase activity and thiobarbituric acid-reactive substance concentrations in the gastric mucosa. Rebamipide suppressed these acidified aspirin-induced gastric lesions and inflammatory changes significantly, and its protective effect was more potent in the case of repeated (twice daily for 3 days) treatment than single treatment before aspirin administration. Immunostaining of zonula occludens (ZO)-1, one of the tight junctional proteins, was strengthened in rat gastric mucosa after repeated administration of rebamipide. In addition, aspirin induced the increasing transport of fluorescine isothiocyanate-labeled dextrans with localized disruption and decreased expression of ZO-1 protein on rat gastric mucosal cell line RGM-1. Rebamipide effectively prevented aspirin-induced permeability changes and disruption of ZO-1 distribution. These results suggest that rebamipide protects against aspirin-induced gastric mucosal lesions by preserving gastric epithelial cell-to cell integrity in addition to the anti-inflammatory effects. Keywords:: aspirin, gastric mucosal injury, tight junction, zonula occludens (ZO)-1, rebamipide